Analisis Kebisingan Dari Kegiatan Penangkaran Burung Walet Di Kelurahan Bagan Kota, Kabupaten Rokan Hilir Dengan Metode Noise Mapping - Aulia, Syarifah Rizky; Sasmita, Aryo; Elystia, Shinta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Bagan Kota has a potential to cause noise from swallow breeding. Local communities that are constantly exposed to noise have the potential to affect people's comfort and health. The purpose of this study was to determine the intensity of outcome noise by swallow breeding, mapping of distribution pattern of noise and noise control prevention. The noise measurement method refers to the noise mapping method and the tool used is the Sound Level Meter (SLM). Measurement based on noise mapping method is carried out for 2 days, that is on Sunday and Monday. The results of the study showed that from 113 measurement points, there were 6 points on Sunday which showed numbers that exceeded the quality standard and 23 points on Monday showed a number that exceeded the quality standard. The highest noise level is 79.01 dB where this point is the source of noise and the lowest noise level of 47.96 dB which is quite far from the noise source. Noise mapping uses the Arcgis 10 program to determine the distribution pattern of noise caused by the noise mapping method. Based on the results of Arcgis 10 shown by different colors, namely red, orange, yellow, light green and dark green. The noise control prevention that can be carried out are engineering control and administrative control.Keywords: Noise, Noise Mapping, Arc.GIS 10, Urban Bagan Village